Diatom fluxes from Young Sound fjord, North-East Greenland - Meri Marianne Mäkelä; Tiia Luostarinen; Sofia Ribeiro; Kaarina Weckström; Mikael K Sejr; Mie Hylstofte Sichlau Winding; Maija Heikkilä (PANGAEA, 2025)
Datasets collected from Young Sound fjord, Northeast Greenland, between 2013 and 2018 were analysed for diatom fuxes. An automated PPS4/3 sediment trap with an aperture of 0.05 m^2 was installed near the fjord entrance (74.322°N; 20.269°W) at 60-m water depth, 15 m above the seafloor as part of the Greenland Ecosystem Monitoring (GEM) programme. The rotation for the trap was set to 7 to 91 -day intervals. Diatoms were counted and identified using a Zeiss Axio Imager.A2 upright research microscope with a Plan-Apochromat 100 exttimes/1.4 oil immersion objective, phase contrast optics and a total magnification of exttimes1000.
In: Mäkelä, MM et al. (2025): Diatom and dinoflagellate cysts determination from Young Sound fjord, North-East Greenland [dataset bundled publication]. PANGAEA, https://doi.org/10.1594/PANGAEA.982994